Creativity in Pedagogical Research – Review of Selected Concepts - Kasprzak, Michalina (Studia Edukacyjne, 2022)
The article attempts to systematize selected concepts of creativity in the field of pedagogical research. Researchers undertake various studies in each area of study due to many aspects, among others, the ambiguity and multidimensionality of the concept of creativity. The paper presents selected approaches to defining creativity and reviews theories concerning psycho-pedagogical aspects of the structure of the creative process.